USE VS ACT, OR WHAT AND HOW IS TESTED IN ENTERING EXEMINATIONS TO UNIVIRSITIES IN RUSSIA AND THE USA - Elena K. Gitman; Mikhail B. Gitman (Высшее образование в России, 2016)
The article offers a comparative analysis for two testing systems: USE (Unified State Examination) introduced in Russia, and ACT (American College Testing) used in the USA. Starting from aims and intentions and followed by organizational aspects, differences in these two systems are discussed in the paper. Dissimilarities concern the final use of the both systems, tested parameters, the number of tests, periodicity of examinations and the time the results are valid. It is underlined in the article, that the main parameters, strongly monitored in the ACT system, are the qualities, defining the readiness of enrollees to study at Universities.